HUBUNGAN ORIENTASI TUJUAN PERSONAL DENGAN KECURANGAN AKADEMIK MAHASISWA FAKULTAS PSIKOLOGI UNIKA SOEGIJAPRANATA - Basilius Oda Sanjaya (IMAGE, 2024)
This research ought to examine the relationship between personal goal orientation and academic cheating of students. The research hypothesis is that there is no correlation between personal goal orientation and academic cheating. The personal goal orientation is broadly divided into two types of personal goal orientations i.e mastery goal and performance goal. The overall personal goal orientation has no direction in correlation with academic cheating. This method of research is quantitative deductive using scale measuring instruments with the student population of three active generations of the faculty of Psychology of Soegijapranata Catholic University, i.e., 2016, 2017, and 2018. Data analyzed by the correlation test product moment. The correlation coefficient obtained is rxy =-0.355 and P = 0.000 (P < 0.01), which means that the study found a very significant negative relationship between personal goal orientation and academic cheating. Master goal orientation has a very significant positive correlation with academic cheating, yet the performance goal has no significant correlation. Higher personal goal orientation predicts lower academic cheating and lower personal goal orientation predict higher academic cheating. The effective contribution is 12.6%., the hypothesis of this research was rejected. Keywords : Personal Goal Orientation, Academic Cheating